Kanal - Centre Pompidou. Brut. - Blistène, Bernard ([S.l.] : Mercatorfonds : Éditions du Centre Pompidou - Fondation Kanal, 2018)
Duchamp, Marcel ; Lovegrove, Ross ; Holzer, Jenny ; Posenenske, Charlotte ; Séchas, Alain ; Judd, Donald ; McCall, Anthony ; Gris, Juan ; Gondry, Michel ; Baldwin, Craig ; Hollein, Hans ; Rauschenberg, Robert ; Papst, Walter ; Shoshan, Assaf ; Plummer Fernandez, Matthew ; Dewasne, Jean ; Prouvé, Jean ; Stenberg, Vladimir A. ; Stenberg, Gueorgii A. ; Raysse, Martial ; Flavin, Dan ; Ito, Toyo ; Van Herpt, Olivier ; Arad, Ron ; Sottsass, Ettore ; Castiglioni, Achille ; Castiglioni, Pier Giacomo ; Araújo, Vasco ; Hyber, Fabrice ; Dijkstra, Rineke ; Haxton, David ; González, Julio ; Acconci, Vito ; Broodthaers, Marcel
Opening Kanal - Centre Pompidou, Brussel, 5 mei 2018
boek